Pendampingan dan Penguatan Peran Orang Tua dalam Membimbing Pembelajaran Daring Anak di Masa Pandemi - Salsa Dilla Ardhana; Supriadi Supriadi; Fatihaturosyidah Fatihaturosyidah; Tiurlina Tiurlina (Jurnal Pengabdian Masyarakat PGSD, 2022)
During a pandemic period, learning assistance for children is really needed, because in the recent time, sometimes children were not optimal in carrying out learning because they do not directly interact with the teacher. In online learning situation, the role of parents is very much needed in guiding children to carry out learning from home. The problem was, there were still many parents who did not understand their role as substitute teachers at home and there are still many parents who did not employ technology or how to use online learning media to assist their children learning. Seeing the situation and potential loss of learning, the authors conducted a student learning assistance program and strengthened the role of parents in guiding children which was carried out at State Elementary School of Tangkolo which is located in Tirtaatmaja Street, Tangkolo RT 25 RW 10 Kabandungan Village, Kabandungan District, Sukabumi Regency. This community service aimed at achieving goals in online learning, as well as accompanying parents in guiding their children to learn from home. The implementation of this program was carried out through introduction and socialization, intensive online assistance for children and parental assistance. Through this activity, parents found it helpful to be able to take advantage of their role as a substitute for the teacher during this online learning and help to motivate children to achieve children's learning. This activity is expected to trigger parental sensitivity to their child's educational situation in the future